"Entrepreneurizing" college programs to increase entrepreneurial intentions: A mediation framework - Mahmoud Ibrahim Fallatah; Tahar Lazhar Ayed (Administrative Sciences, 2023)
The impact of entrepreneurship on the development of emerging economies is widely recognized. Research has focused on studying factors that increase entrepreneurship in societies, including the role of education in increasing entrepreneurial intentions among students. In this paper, we contribute to the entrepreneurship and education literature by examining the impact of entrepreneurial college programs on entrepreneurial intentions. Further, we study the mediating roles of perceived benefits and individual creativity. Using a sample of 438 students from a public university in Saudi Arabia, our findings reveal that students enrolled in entrepreneurial programs have higher levels of entrepreneurial intentions that those enrolled in non-entrepreneurial programs, and that perceived benefits and individual creativity partially mediate the aforementioned relationship. The paper opens the door for future research in the entrepreneurship and education literature and provides several managerial implications.
Keywords: 350; education; entrepreneurial intentions; entrepreneurship; individual creativity; perceived benefits; Saudi Arabia